Antioxidant Natural Plant Constituents for Diabetic Wound Repair - Meng, Lele; Zhang, Xueying; Sun, Li; Chen, Long (MedComm - Biomaterials and applications, 2025)
ABSTRACT Diabetes mellitus is a prevalent metabolic disorder characterized by a prolonged hyperglycemic state, which can result in complications affecting multiple organ systems. Among these complications, impaired wound healing in diabetic patients poses a significant challenge, leading to considerable suffering and economic burden. This issue has emerged as one of the major challenges in global healthcare, where oxidative stress, bacterial infections and chronic inflammation are critical contributing factors. Antioxidant compounds derived from natural plants are increasingly being explored in diabetic wound healing research due to their beneficial biological properties. These botanical components effectively scavenge excessive reactive oxygen species and mitigate cellular damage associated with oxidative stress. By controlling bacterial infections, inhibiting pro‐inflammatory cytokines, and enhancing the activity of antioxidant enzymes, these compounds not only improve the wound microenvironment but also directly promote the proliferation and migration of fibroblasts and keratinocytes, thereby facilitating tissue regeneration. This paper examines the modulation of oxidative stress, control of bacterial infections, the impact on inflammatory responses, and the promotion of wound repair, with a focus on the application of specific antioxidant plant components in diabetic wound healing, delivery systems, and clinical applications, as well as challenges and future directions. Antioxidant natural plant constituents promote diabetic wound repair by ameliorating oxidative stress, inhibiting inflammatory responses, and promoting tissue regeneration.